Corilagin prevents non-alcoholic fatty liver disease via improving lipid metabolism and glucose homeostasis in high fat diet-fed mice - Liao, Mingjuan; Zhang, Rong; Wang, Yongling; Mao, Ziming; Wu, Jing; Guo, Huaqi; Zhang, Kaiwen; Jing, Yu; Zhang, Caoxu; Song, Huaidong; Chen, Xia; Wei, Gang (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) has been considered to be one of the most common chronic liver diseases. However, no validated pharmacological therapies have been officially proved in clinic due to its complex pathogenesis. The purpose of this study was to examine the protective effects of Corilagin (referred to Cori) against NAFLD in mice under a high fat diet (HFD) condition. Mice were fed either a normal control diet (NCD) or HFD with or without Cori (5 or 10 mg/kg body weight) for 15 weeks. In our results, Cori treatment significantly attenuated HFD-induced hepatic steatosis, high NAFLD activity score (NAD) and liver injury. Consistently, Cori treatment remarkably alleviated HFD-induced hepatic lipid accumulation (e.g., triglycerides (TG) and total cholesterol (TC) contents in liver), and improved plasma lipid concentrations (e.g., plasma TG, TC, low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c)). Moreover, Cori treatment ameliorated NAFLD associated metabolic disorders such as glucose intolerance and insulin resistance in HFD-fed mice. Additionally, Cori treatment dramatically changed HFD-induced liver gene expression profiles, and identified overlapped differentially expressed genes (DEGs) between NCD vs. HFD group and HFD vs. HCR (high fat diet plus treatment with Cori) group. With these DEGs, we observed a marked enrichment of Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, which were closely associated with the metabolic balance in liver. Particularly, we found several potential hub proteins against NAFLD development with analyses of protein-protein interaction (PPI) network and qPCR assays. Collectively, our results revealed the important protective effects of Cori against the progress of NAFLD, which was probably mediated through improving dysregulated lipid metabolism and insulin resistance in HFD-fed mice. Additionally, Cori-dependent overlapped DEGs might serve as a featured NAFLD-associated gene expression signature for the diagnosis, treatment, as well as drug discovery and development of NAFLD in the near future.